Determination of the drag coefficient of lattice structures under wind load using porous media approach - Pezo, Milada; Mirkov, Nikola; Bakic, Vukman (Thermal science, 2022)
The power transmitters, guyed masts and other lattice structures are exposed to wind action. The aerodynamic forces acting on tall tower constructions have crucial importance on the stability of the structure. The lattice structure drag coefficient determination is the subject of the international standards ESDU 81027 and 81028 and Eurocode 3 Part 3.1, but it can also be determined by numerical methods. For that purpose modelling using CFD proved to be both accurate and reliable. In this study the fluid-flow around the segment of a power transmitter was simulated by a 3-D model, where the geometry of the segment is approximated with a porous structure having the appropriate factor of porosity, in order to simplify the geometry. We have used three representative models of turbulence, standard k-? model, RNG k-? model, and Reynolds stress model. Drag coefficient values are extracted from the flow field and compared for all studied cases and with available experimental results from the wind tunnel. Simulations were performed for four wind velocities between 10 m/s and 30 m/s. The results are supplemented by the ones obtained by artificial neural network. The aim of this study is to show how the simple turbulence model coupled with approximated geometry can be used in the analysis of the aerodynamic forces acting on the lattice structure.